THE DEVELOPMENT OF AUDIT ACTIVITY IN UKRAINE FOR THE EUROPEAN INTEGRATION PROCESSES - N. Dorosh (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The author in the article analyzes the audit activity in Ukraine and the main directions of audit and audit services. In addition in the article identified the factors that affect these processes. Procedure “Due diligence” was disclosed as a species related services to inform decisions about the acquisition, mergers, acquisitions and investments. The author made the conclusions on the further development of audit and comparatived Act Sarbanes – Oxley and Directive 2014/56 EU, concerning their orientations and common provisions. It was established that for the European integration processes in Ukraine need to create a рublic oversight system of audit firms of public-interest entities, including public oversight authority and noting its functions and powers. The basic provisions of the draft law of Ukraine “On Auditing” were revealed, what have the European integration character.